Model Minat Kunjungan Wisata Berdasarkan Lingkungan Fisik, Sikap dan Norma Subyektif - Mohammad Amin (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2020)
The purpose of this study was to examine and analyze the influence of the physical environment, attitudes and subjective norms on the interest of visiting tourists in Ora Beach. The population of this study are all domestic and foreign tourists who while visiting Ora Beach tourism objects from the period of February to March 2019. Sampling using accidental sampling technique with a final sample of 49 respondents. Analysis of research data using Multiple Linear Regression Analysis. The results showed that the physical environment, attitudes and subjective norms proved to have a positive and significant effect on the interest of visiting tourists in Ora Beach. This can be proven through the regression coefficient of the physical environment and attitude which shows that if the value of the physical environment, attitudes and subjective norms increase, the increase will be followed by an increase in tourist interest in visiting Ora Beach. Thus it can be said that increasing the value of the physical environment, attitudes and subjective norms will increase the interest of tourists visiting Ora Beach.